Prototype Design of Unmanned Surface Ship to Detect Illegal Fishing Using Solar Power Generation Technology - Yudhi Ardiyanto; Iwan Tri Sujoko; Wicaksono Aji Wibowo; Vendy Dwi Hendra Nugraha; Faiz Evan Saputra (Journal of Electrical Technology UMY, 2019)
This paper describes the prototype and implementation of the unmanned surface ship to detect illegal fishing using solar power generation technology. Indonesia, one of the Southeast Asian countries, has some of the world’s most productive fishing grounds. Under the leadership of President Joko Widodo, Indonesia has launched a severe crackdown on illegal fishing in its waters. The color tracking technique is the capability to take a picture, segregate a specific color, and extricate data regarding the location of that picture containing merely that color. Whilst processing the pixels in a vision, the CMUcam5 controls a counter that keeps tracking the number of consecutive pixels in the current row before being within the tracked color bounds. The current pixel is marked as a tracked pixel only when the value is higher than the noise filter value. The team has developed innovative features to complete the program. The features are double hull and propulsion design, automatic cooling system, automatic camera scanning using pixy CMUcam5 for image processing, Webcam video camera, voice command with system recognition intelligent software, fuel engine speed maximum 50 km/h, double fin, solar panel for supply battery, and computerized control. In the screen base station, we can see the situation of PTS Siluman Ship from serial communication microcontroller, serial communication image processing CMUCam 5, video webcam, GPS, and compass. All of the data from PTS Siluman Ship are sent online.